EFFECT OF SPRAYING WITH TRYPTOPHAN AND GLYCINE ON PROTEOTYPE ESTIMATION OF KUMQUAT AND LOCAL LEMON SEEDLINGS (British Journal of Global Ecology and Sustainable Development, 2023)
This study was conducted in the cloth canopy of the College of Agriculture, University of Basrah, during the growing season 2021-2022 on seedlings of kumquat and local lemon, totaling 54, 27 seedlings for each plant type, in three replications, as the seedlings were sprayed six times with three concentrations (0, 50, 100) mg l-1 of the amino acids tryptophan and glycine. The most important results of the study were the appearance of between (3-8) protein bundles depending on the type and conditions of treatment. The number of protein bundles differed between the comparison treatments for the two types of kumquat and lemon seedlings, as the comparison treatment of lemon seedlings showed 7 protein bundles, while 8 protein bundles appeared in the treatment; in comparison to kumquat seedlings, there were 6 protein bundles in the G50 treatment for both types. The treatment with tryptophan at a concentration of 100 mg l-1 caused some protein bundles to disappear, and only three protein bundles remained in the kumquat leaves for treatment T100 and G50.